Evaluation of Emergency Access Evacuation Routes Using Agent-Based Model Application - Irfan Yusuf Muttaqien; Stephen Tanugraha; Julia Eka Puspitaningrum; Hansen Abdi Wibisono Manik (Universitas Atma Jaya Yogyakarta, 2024)
One vital component in managing buildings, such as houses or buildings, is the implementation of safety measures against disaster risks. Artificial Intelligence (AI) technology can minimise fire risk in buildings. The integration of AI technology enables early detection, rapid response, and even realistic evacuation simulations to increase the efficiency of security systems and protect against disasters. This research aims to review a program based on Agent-Based Artificial Intelligence called AnyLogic to calculate the efficiency of emergency access evacuation routes. The research uses the journal review method as the primary approach. This method is part of systematic research on certain phenomena and collects data from related journal sources. This research concludes that AnyLogic is crucial in optimising emergency access evacuation strategies in multiple contexts. AnyLogic has the advantage of determining the most efficient evacuation route, determining evacuation time, and being able to evaluate evacuation routes in certain buildings.